Subinhibitory Concentrations of Triclosan Promote Streptococcus mutans Biofilm Formation and Adherence to Oral Epithelial Cells - Lombardo Bedran, Telma Blanca [UNESP]; Grignon, Louis; Spolidorio, Denise Palomari [UNESP]; Grenier, Daniel (Public Library Science, 2014)
Triclosan is a general membrane-active agent with a broad-spectrum antimicrobial activity that is commonly used in oral care products. In this study, we investigated the effect of sub-minimum inhibitory concentrations (MICs) of triclosan on the capacity of the cariogenic bacterium Streptococcus mutans to form biofilm and adhere to oral epithelial cells. As quantified by crystal violet staining, biofilm formation by two reference strains of S. mutans was dose-dependently promoted, in the range of 2.2- to 6.2-fold, by 1/2 and 1/4 MIC of triclosan. Observations by scanning electron microscopy revealed the presence of a dense biofilm attached to the polystyrene surface. Growth of S. mutans in the presence of triclosan at subMICs also increased its capacity to adhere to a monolayer of gingival epithelial cells. The expression of several genes involved in adherence and biofilm formation in S. mutans was investigated by quantitative RT-PCR. It was found that subMICs of triclosan significantly increased the expression of comD, gtfC, and luxS, and to a lesser extent of gtfB and atlA genes. These findings stress the importance of maintaining effective bactericidal concentrations of therapeutic triclosan since subMICs may promote colonization of the oral cavity by S. mutans.